2021
DOI: 10.47405/mjssh.v6i9.993
|View full text |Cite
|
Sign up to set email alerts
|

Exploring ESL Teachers’ Insights on Corrective Oral Feedback in a Malaysian Secondary Education Context

Abstract: Feedback is one of the most significant elements in the process of teaching and learning. It serves as a tool to enhance students’ second language proficiency. Thus, the purpose of this study is to investigate how oral feedback is viewed and how it has been maneuvered to assist second language learner’s linguistic competence from the viewpoint of English teachers. Teachers’ perception of feedback is very important because it will determine the amount of feedback used in the process of teaching and learning. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…As a result, teachers and students have adopted a repressive attitude towards it. Fadzil and Said (2021) addressed Malaysian teachers' perspectives on OCF and reported that OCF serves as an instrument for motivating learners to learn the language. The teachers noticed that the student's competence is enhanced through the feedback.…”
Section: Problem Statementmentioning
confidence: 99%
“…As a result, teachers and students have adopted a repressive attitude towards it. Fadzil and Said (2021) addressed Malaysian teachers' perspectives on OCF and reported that OCF serves as an instrument for motivating learners to learn the language. The teachers noticed that the student's competence is enhanced through the feedback.…”
Section: Problem Statementmentioning
confidence: 99%